Cognitive Bias and the Extraversion Personality Shaping the Behavior of Investors - Ishfaq, Muhammad; Nazir, Mian Sajid; Qamar, Muhammad Ali Jibran; Usman, Muhammad (Frontiers in Psychology, 2020)
This paper examined direct and indirect effects (via investors’ risk perception) of heuristic biases on investors’ irrational behavior in decision making. Importantly, this study also examined the moderating effect of investors’ personality trait – extraversion – on both direct and indirect association between heuristic biases and irrational decision making. Based on survey data collected from 247 investors registered in various brokerage houses in Pakistan and analyzed using Hayes’ PROCESS macro for SPSS, the results of this study revealed that heuristic biases positively affect investors’ irrational decision making, both directly and indirectly, via risk perception. Interestingly, the results showed that extraversion moderated both direct and indirect associations between heuristic biases and investors’ irrational behavior in decision making. Our findings carry useful practical implications for organizations’ policymakers.